A critical and reflective commentary on a portfolio of compositions - Slater, Angela Elizabeth (2016)
This thesis consists of a portfolio of nine compositions accompanied by a written commentary and (where possible) audio recordings of these pieces. The compositions span a variety of instrumentations from large orchestral works to solo and chamber works. In the accompanying commentary I discuss the technical foundations of my compositional language, examining selected aspects of my gestural, harmonic, and timbral language to shed light on my creative process. The development and prominence of each of these aspects is discussed, with particular emphasis on the evolution of my timbral language. I demonstrate how I use extra-musical stimuli to determine compositional parameters for various musical elements affecting large-scale structures, gestural, harmonic and timbral language and more broadly the aesthetic impulses of a piece. As part of this, I discuss the importance of a concept that feeds into a work’s title to help determine various structural elements. I also explain how the views and thoughts of composers such as Kaija Saariaho, Arlene Sierra, Thomas Adès and Dai Fujikura have helped shape my approach to extra-musical stimuli.